'Getting the best of both worlds': aspirations and agency in relation to marriage and schooling among Haalpulaar women in northern Senegal. Issue 8 (17th November 2021) - Newman, Anneke
ABSTRACT: The link between marriage and premature school-leaving among females in the Global South is a major preoccupation within the field of international development and education, yet theoretically-grounded qualitative scholarship unpacking this relationship remains scarce. This paper uses models developed to conceptualise female agency in constrained circumstances, combined with theory on youth's educational aspirations, to analyse several ethnographic case studies of the ways female pupils in northern Senegal attempted to 'get the best of both worlds', namely fulfiling the competing ideals of marrying and finishing secondary school. Findings are used to inform recommendations to guide future research, policy and programming on marriage and premature school-leaving in the Global South more widely.